decision support system for soil and water conservation measures on agricultural watersheds - Sarangi, A; Madramootoo, C.A; Cox, C (Land degradation & development, 2004)
Integrated watershed management (IWM) is vital in achieving agricultural sustainability in terms of both production and environmental protection. A decision support system (DSS) is useful in generating alternative decision scenarios for management of natural resources, facilitating the implementation of IWM concepts in an interactive and holistic way. The decision to implement an appropriate land use coupled with suitable soil and water conservation techniques not only enhances watershed health but also prevents sediment losses. Besides reducing basin fertility, such losses decrease the storage capacity of downstream reservoirs through silt deposition, which can, in turn, give rise to low biomass production and poorer flood control. In order to facilitate IWM, an effort was made to develop, in the Visual Basic programming language, a soil and water conservation DSS which considered both structural and cropping practices for arresting sediment loss. Input parameters to the DSS for a given tract of land included: mean slope; sediment loss; soil type; and land capability class (LCC). Outputs included decision criteria to choose among alternative structural measures and suggested cropping systems to serve as biological measures to reduce soil loss and conserve water. Structural watershed management measures included a variety of soil and water conservation structures widely adopted by farming communities throughout the world. The DSS is capable of providing sediment control solutions not only for small watersheds but also for larger drainage basins, by dividing the basin into smaller watersheds. The DSS was validated for a watershed on the Caribbean island of St Lucia and used to suggest measures for a 10° slope under specific soil type, sediment loss and LCC conditions. The measures proposed included bench terraces, graded contour bunds, conservation ditches, concrete chute spillways, diversion dams and conservation cropping systems. The measures actually adopted on‐site were conservation ditches, graded contour bunds and conservation cropping systems, a close parallel to the DSS's proposed measures. On slopes ranging from 5–55°, implementation of the suggested control measures resulted in a 34–37 per cent reduction in soil loss on the watershed. Copyright © 2004 John Wiley & Sons, Ltd.